EFEKTIFITAS KREASI NILAI DAN STRATEGI BAURAN PEMASARAN TERHADAP DAYA SAING PERUSAHAAN KOSMETIK DI WILAYAH JAKARTA - Elfrida V Napitupulu (Jurnal Manajemen, 2018)
This study aims to test the factors of value creation and marketing mix both single and simultaneously and  its relationship with the competitive advantage for  the cosmetic industries in Jakarta. This study refers to the fact finding of the high interest of customers to utilize cosmetics as to beautify themselves. There are  high competition amongts  the industries to win the competition. The results show that the value creation program and marketing mix program can be impacted significantly by cosmetic customers in Jakarta. In addition, it was found that the factors of value creation and marketing mix significantly affect the competitive advantage of the cosmetics industry in Jakarta. Thus it is expected that the level of loyalty of cosmetic customers will be higher as well as the customer will trust the brands consistently.  Keyword : value creation, marketing mix, competitive advantage, cosmetics, costumer